2007
DOI: 10.1007/s10750-007-9176-0
|View full text |Cite
|
Sign up to set email alerts
|

Response of epiphytic algae to nutrient loading and fish density in a shallow lake: a mesocosm experiment

Abstract: Studies on the effect of eutrophication on the ecology of shallow lakes, usually pay scant attention to changes within the epiphytic algal community, though the contribution of this to the ecosystem dynamics is transcendental. In order to test the influence of nutrient loadings and fish densities in the structure of algal epiphyton in a shallow lake, an experiment was performed using in situ mesocosms. Nutrient additions were related to significant decreases in the total epiphyton biovolume and that of bacilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
12
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 63 publications
6
12
0
2
Order By: Relevance
“…Despite some differences among the lakes in the number of species and algal abundance, we found that the diversity of algal assemblages based on abundance did not differ one from the other and was lower than, for example, in the meso-eutrophic Lake Gulbinas (Karosienė and Kasperovičienė, 2008). However, the diversity based on the algal biomass was found to be the highest in the least eutrophicated lake, which is in accordance with the results of a mesocosm experiment by Blanco et al (2008). They revealed that species richness of epiphyton on the submerged Myriophyllum alterniflorum decreased significantly (from 15 to 32 taxa) with N and P enrichment.…”
Section: Parameterssupporting
confidence: 88%
See 2 more Smart Citations
“…Despite some differences among the lakes in the number of species and algal abundance, we found that the diversity of algal assemblages based on abundance did not differ one from the other and was lower than, for example, in the meso-eutrophic Lake Gulbinas (Karosienė and Kasperovičienė, 2008). However, the diversity based on the algal biomass was found to be the highest in the least eutrophicated lake, which is in accordance with the results of a mesocosm experiment by Blanco et al (2008). They revealed that species richness of epiphyton on the submerged Myriophyllum alterniflorum decreased significantly (from 15 to 32 taxa) with N and P enrichment.…”
Section: Parameterssupporting
confidence: 88%
“…The direct periphytic biomass consumption by omnivorous fish was showed in experimental study by Guariento et al (2010). Blanco et al (2008) showed that zooplanktivorous fish enhanced the abundance of Euglenophyceae and Zygnematophyceae, as well as algal species richness and diversity, by secreting biogenic substances. Our studies showed that the abundance of crustaceans being able to graze on algae was very low, and no significant relationship between them and epiphytic algae was found.…”
Section: Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…abiotic spatial factors and catchment variables as landuse and hydromorphology (Gottschalk and Kahlert, 2012), physical and chemical quality of substratum Michelutti et al, 2003;Poulíčková et al, 2003Poulíčková et al, , 2004King et al, 2006;Ács et al, 2007;Bolla et al, 2010), light conditions (Kelly et al, 1998;King et al, 2006), seasonality (King et al, 2002(King et al, , 2006Bolla et al, 2010;Rimet et al, 2015), water chemistry (Hofmann, 1994;King et al, 2000;Schönfelder et al, 2002;Kitner and Poulíčková, 2003;Blanco et al, 2004;Ács et al, 2005;Stenger-Kovács et al, 2007;Jüttner et al, 2010;Gottschalk and Kahlert, 2012) and also other groups of organisms, such as indirect effect of fish (Blanco et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, biofilms are sensitive to changes in environmental conditions. Thirdly, they potentially constitute an important step in the integration of biogeochemical cycles and dynamics of aquatic ecosystems (Schorer and Eisele 1997;Allan and Castillo 2007). Most important of all is that they play a key role in energy transduction and uptake or retention of nutrients (Sabater et al 2000).…”
Section: Introductionmentioning
confidence: 99%